2011
DOI: 10.1523/jneurosci.3297-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Experience Decreases Drug-Induced Reinstatement of Morphine CPP in Adulthood via Microglial-Specific Epigenetic Programming of Anti-Inflammatory IL-10 Expression

Abstract: A critical component of drug addiction research involves identifying novel biological mechanisms and environmental predictors of risk or resilience to drug addiction and associated relapse. Increasing evidence suggests microglia and astrocytes can profoundly affect the physiological and addictive properties of drugs of abuse, including morphine. We report that glia within the rat Nucleus Accumbens (NAcc) respond to morphine with an increase in cytokine/chemokine expression, which predicts future reinstatement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
163
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(177 citation statements)
references
References 54 publications
(61 reference statements)
13
163
1
Order By: Relevance
“…In a similar manner, an acute injection of morphine rapidly increases mRNA expression of both microglial CD11b and astrocytic GFAP in the NAc, but not the hippocampus (Schwarz et al, 2011). Concomitant systemic treatment with a pharmacological modulator of glial activation such as ibudilast, which functions as a nonselective phosphodiesterase inhibitor but has broad effects on glial function (Gibson et al, 2006), is effective at preventing CD11b and GFAP induction by morphine ), a result replicated by targeted intra-NAc infusions of ibudilast (Schwarz et al, 2011). Minocycline, a highly lipidsoluble tetracycline antibiotic that can also modulate glial activity, is capable of preventing LPS-induced upregulation of microglial Iba1 but has no effect on astrocytic GFAP upregulation following LPS (Yoon et al, 2012).…”
Section: Opioids Glia and Neuroimmune Signalingmentioning
confidence: 76%
See 3 more Smart Citations
“…In a similar manner, an acute injection of morphine rapidly increases mRNA expression of both microglial CD11b and astrocytic GFAP in the NAc, but not the hippocampus (Schwarz et al, 2011). Concomitant systemic treatment with a pharmacological modulator of glial activation such as ibudilast, which functions as a nonselective phosphodiesterase inhibitor but has broad effects on glial function (Gibson et al, 2006), is effective at preventing CD11b and GFAP induction by morphine ), a result replicated by targeted intra-NAc infusions of ibudilast (Schwarz et al, 2011). Minocycline, a highly lipidsoluble tetracycline antibiotic that can also modulate glial activity, is capable of preventing LPS-induced upregulation of microglial Iba1 but has no effect on astrocytic GFAP upregulation following LPS (Yoon et al, 2012).…”
Section: Opioids Glia and Neuroimmune Signalingmentioning
confidence: 76%
“…Importantly, these measures of glial activation are not found across the entire brain, but are rather restricted within certain brain regions, including the VTA, dentate gyrus, periaqueductal gray, dorsal caudate, and other regions that have previously been associated with opioid dependence . In a similar manner, an acute injection of morphine rapidly increases mRNA expression of both microglial CD11b and astrocytic GFAP in the NAc, but not the hippocampus (Schwarz et al, 2011). Concomitant systemic treatment with a pharmacological modulator of glial activation such as ibudilast, which functions as a nonselective phosphodiesterase inhibitor but has broad effects on glial function (Gibson et al, 2006), is effective at preventing CD11b and GFAP induction by morphine ), a result replicated by targeted intra-NAc infusions of ibudilast (Schwarz et al, 2011).…”
Section: Opioids Glia and Neuroimmune Signalingmentioning
confidence: 91%
See 2 more Smart Citations
“…Finally, an epigenetic neuroimmune link to abuse liability following maladaptive early life experiences has been established. Schwarz et al (2011) demonstrated that early life events in rodents caused specific adaptions in the methylation of the IL-10 gene within nucleus accumbens microglia, which in turn, was associated with an increase in morphine's rewarding properties. 23…”
Section: Evidence For Neuroimmune System Involvement In Addictionmentioning
confidence: 99%